Developing Task-Based Reading Materials Using Short Stories to Promote Critical Thinking in EFL Students’ Extensive Reading Classes - Terasne, Terasne; Hanan, Ahmad; Nafisah, Bq. Zuhrotun (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2025)
This study developed task-based reading materials using short stories to enhance EFL students’ critical thinking, particularly inference and evaluation, in the Extensive Reading course. Employing a Research and Development (R&D) design, 60 fifth-semester students of the English Education Study Program at Universitas Pendidikan Mandalika were assigned to an experimental group (n = 30) and a control group (n = 30). Data were obtained through validation checklists, pre- and post-tests, and questionnaires. The results showed that the materials were valid (77,5%), practical (81% of students achieved the minimum passing grade), and effective, with the experimental group significantly outperforming the control group (t (58) = 3,99, p < ,001, d = 1,03). The implementation fostered active participation, critical discussion, and substantial improvement in inference and evaluation skills. These findings highlight the importance of integrating Task-Based Learning with short stories as an effective approach to promote critical literacy in university-level extensive reading instruction.